Determination of the optimallogarithmic model for the data of the contingency tables with a practical application in the field of road accidents (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Road accidents are random or accidental incidents that are subject to intermittent distributions ,the most important distributions are (binomial distribution , Poisson distribution , negative binomial distribution) , these incidents are categorical according to the nature of the accident (fatal, fatalwith wounded , wounded only), in this research , we considered the impact of the type of accident (collision , overturned , run over ) and the scene (inside the city , outside the city ) and it,s impact on the nature of the incident individually on the one hand and on the other hand using the contingency tables of class (r×c×k) and estimate the logarithmic model for each case and selecting the optimalmodel by adopting the maximum likelihood ratio using road accident data in the holy province ofKarbala .